Organização temporal da leitura oral na doença de Parkinson - Erica Goncalves Teixeira (2008)
This study aimed at analyzing speech temporal organization in Parkinsons disease (PD), specifically speech rate, pauses, silence rate of plosive consonants and disfluencies, verifying interference of levodopa in prosodic parameters from readings at different rates (normal, slow and fast), compared to a group which did not have such disease. Ten individuals with PD were recorded when reading a passage from EUROM1: five males and five females, and ten individuals who did not have PD (control group - CG). Recordings of the group with PD were carried out in two moments: experimental group which was not under medicine effect (EG off) and experimental group under the medicine effect (EG on). In CG, the recordings were carried out in only one moment. The informants were asked to read in three modalities: normal reading (NR), slow reading (SR) and fast reading (FR), in this order. For the temporal organization analysis, we studied the following parameters: time of elocution (TE) and time of articulation (TA), number of pauses (NP) and time of pauses (TP), number of syllables (NS), elocution (ER) and articulation rate (AR). Plosives time of silence was manually marked with the spectogram and oscilogram, and disfluencies were identified as: repetitions, filled pauses, false beginning, lingering, omissions and adds. The data were acoustically analyzed on Praat 4.4.27 and statistically in Microsoft Excel 2000 and Minitab 15. From data analysis, we could note that EG had a slower speech rate than CG, when carrying out a NR. In SR, EG slows down more efficiently, and in FR, EG accelerates less efficiently, compared to CG. After informants took levodopa, we noted that there was an improvement on the analyzed parameters, but even so, their performance was inferior than of CG. As to pauses, they were mostly found between periods and had shorter length within the periods, for the analysis of NR. In the different reading modalities, results from male individuals did not have statistically significant differences between the groups. Such finding evidenced that the fact that an individual who has PD and takes levedopa or not does not lead him to apply the parameter differently to change the reading modality. For female individuals, when carrying out NR, pauses lasted longer for EG off. In analyses referring to plosives time of silence, durations were reduced in CG, a little more in EG on and higher values in EG off, which reinforces the efficiency of levedopa for such parameter. The occurrence of disfluencies was greater in EG off, so that it is possible for us to verify that PD disturbs efficient communication and this disability is attenuated by taking levedopa, which does not lead to a performance as good as of CG.